The development of a tertiary level visual communication module incorporating an art appreciation approach / Maithreyi Subramaniam - Maithreyi , Subramaniam (2017)
The central purpose of this study was to build and examine a tertiary visual communication module incorporating an art appreciation approach, a unit in graphic design and multimedia programme offered as an integral part of a subject of instruction in art education for tertiary level. The majority of the art educators is facing problems related to art appreciation. They have only been emphasizing studio art production and have no background knowledge in preparing a teaching module. The quantitative research design and procedures were employed in this study. An experimental research using the quasi-experimental design that is a single-group interrupted time series-design was used to examine a group of students’ achievement. The samples in this study were 35 (N=35) students enrolled visual communication unit in the first year of graphic design and multimedia programme. The research was conducted at the researcher’s university, one of a private institution located in Petaling Jaya, Selangor. In collecting the data, two instruments were used, namely the tertiary level visual communication module and five sets questions of tests. A reliability test was conducted on both instruments to test the validity, consistency and reliability of the data analysis procedure as the tertiary level visual communication module and five sets questions of tests using Cronbach’s Alpha reliability test 0.5. The descriptive statistics made use of means, standard deviations and percentage to determine the students’ achievements. The inferential statistics, repeated measure ANOVA was employed to investigate the changes in mean scores over five time points both for five sets questions of tests mean score and lessons (studio art production) mean score. The findings exhibited that the students have expected developmental progression in their five sets questions of tests. In terms of lessons (studio art production), students were able to make an appreciation of their studio art production. The tertiary visual communication module incorporating an art appreciation approach impacted the quality of students’ development of selection of skills in visual perception and artistic response, investigations in terms of historical, cultural and social context, engaging students with the art-making process and enhancing their critical and aesthetic inquiry for a better understanding, aesthetic appreciation and an increase of self-expression. Overall, the students’ lessons (studio art production) and tests score exhibited students has gained very good knowledge through the tertiary level visual communication module. The effectiveness of module exhibited students’ better understanding and foster proficiency in implementing thinking both in their five sets questions of tests and lessons (studio art production)